1985
DOI: 10.1021/bi00334a028
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of lysine formation by meso-diaminopimelate decarboxylase from wheat germ: use of proton-carbon-13 NMR shift correlation to detect stereospecific deuterium labeling

Abstract: The stereochemical course of the wheat germ meso-diaminopimelate (DAP) decarboxylase reaction is compared to that of the decarboxylase isolated from Bacillus sphaericus, which has been reported to proceed with an unusual inversion of configuration [Asada, Y., Tanizawa, K., Sawada, S., Suzuki, T., Misono, H., & Soda, K. (1981) Biochemistry 20, 6881-6886]. Reaction of each enzyme with either unlabeled diaminopimelic acid in D2O or [2,6-2H2]diaminopimelic acid in H2O gave stereospecifically deuterium-labeled lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 36 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…However, these in vitro effects were not translated into conspicuous antibacterial effects: none of the isomers of 3 or 4 caused any inhibition of growth when tested against a series of organisms on defined media on plates; only 4c inhibited slightly B. subtilis growth at high doses (->350 p,g per test disc) [11]. On the other hand, it was shown that A2pm auxotrophs could grow, in the presence of lysine, with exogenous lanthionine ( [15], and references therein), the meso isomer of the sulfur amino acid being incorporated into peptidoglycan [15].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, these in vitro effects were not translated into conspicuous antibacterial effects: none of the isomers of 3 or 4 caused any inhibition of growth when tested against a series of organisms on defined media on plates; only 4c inhibited slightly B. subtilis growth at high doses (->350 p,g per test disc) [11]. On the other hand, it was shown that A2pm auxotrophs could grow, in the presence of lysine, with exogenous lanthionine ( [15], and references therein), the meso isomer of the sulfur amino acid being incorporated into peptidoglycan [15].…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, the synthesis of stereochemically defined N-hydroxy analogues would be of great interest. Previously, we showed that the mixture of isomers 10 was an alternative substrate for A2pm dehydrogenase from B. sphaericus (22% velocity relative to meso-A2pm), a moderate inhibitor of LysA from B. sphaericus (Ki = 0,91 mM) and a very potent inhibitor of DapF from E. coli (Ki =5.6 ~tM); it inhibited by 75% the growth of B. megaterium at 20 ~g m1-1, and totally that of B. subtilis at 500 p.g m1-1 [5,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations